Case report: A case of corneal deposits between binocular descemet membrane and corneal endothelial layer after small-incision lenticule extraction (SMILE) followed by HPV vaccine - Zhang, Hao; Deng, Yingping; Ma, Ke; Sun, Chengshu; Tang, Jing (Frontiers in Medicine, 2022)
Background Deposits located between the Descemet memberane and the corneal endothelial layer in both eyes has not yet been reported after SMILE. Case report Grayish white fine deposits was found between the Descemet memberane and the corneal endothelial layer in both eyes of the patient's cornea, and no other abnormalities were observed in the anterior and posterior segments of patient's eyes with ophthalmic examination instrument. However, the visual acuity of patient remained unchanged. Significantly, the patient had a sister who had undergone the same procedure a year earlier without any complications. After careful questioning, we learned that the patient received the 9-valent human papillomavirus (HPV) vaccine on the third post-operative day without any other special experiences. We performed immunological examination and genetic testing on the patient. The results of immunological examination of patient showed no obvious abnormality, which was consistent with the routine trend after vaccination. In particular, a homozygous variation of the ARSG gene was found in the patient and her sister. Conclusion There are two possible causes of corneal changes in patients. The first is IGA elevation caused by vaccination, deposited in the cornea. Second, the ARSG gene mutation of the patient leads to a potential congenital corneal dystrophy, and clinical manifestations occur under the stimulation of the vaccine.